Osteonecrosis of the maxilaries associated with use of biphosphonate - Lacerda, Jamille dos Passos (2019)
Introduction: Bisphosphonates (BF) are inhibitors of reabsorption bone and are indicated for the treatment of Osteoporosis, Bone Metastasis, Multiple Myelomas and Paget's Disease. They are pyrophosphate analogs, which have high affinity for bone tissue inhibiting the action of osteoclasts. Although it has benefits for patients with of such diseases by assisting, for example, in the pain control prolonged use may lead to osteonecrosis of the jaws. Objectives: This article aims to review themedical literature on the use of bisphosbonates and dental surgeries. Materials and Methods: The indexed articles google academico and PubMed were scanned and the articles with the highest impact factor were selected. Results: We found 350 articles and selected 20 with the highest impact factor. Conclusion: Bisphosphonates are substances that can cause oteonecrosis in patients undergoing invasive dental treatments.